2010
DOI: 10.1038/ajg.2010.171
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Dysplasia in Barrett's Esophagus: Overdiagnosed and Underestimated

Abstract: LGD in BE is an overdiagnosed and yet underestimated entity in general practice. Patients diagnosed with LGD should undergo an expert pathology review to purify this group. In case the diagnosis of LGD is confirmed, patients should undergo strict endoscopic follow-up or should be considered for endoscopic ablation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
323
3
19

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 428 publications
(353 citation statements)
references
References 41 publications
8
323
3
19
Order By: Relevance
“…Th e importance of the confi rmation of the diagnosis of LGD comes from two recent studies from the Netherlands. Review by two GI pathologists, with extensive experience in the diagnosis of BE-related neoplasia, found that of 147 patients diag nosed with LGD in the community, 85% of the patients were downgraded to a diagnosis of no dysplasia ( 122 ). Further work by that group examined 293 additional patients with LGD diagnosed in the community who had biopsies reviewed by at least 2 GI pathologists and 73% of the cases were downgraded to indefinite for dysplasia or nondysplastic BE ( 123 ).…”
Section: Advanced Endoscopic Imaging Techniquesmentioning
confidence: 99%
“…Th e importance of the confi rmation of the diagnosis of LGD comes from two recent studies from the Netherlands. Review by two GI pathologists, with extensive experience in the diagnosis of BE-related neoplasia, found that of 147 patients diag nosed with LGD in the community, 85% of the patients were downgraded to a diagnosis of no dysplasia ( 122 ). Further work by that group examined 293 additional patients with LGD diagnosed in the community who had biopsies reviewed by at least 2 GI pathologists and 73% of the cases were downgraded to indefinite for dysplasia or nondysplastic BE ( 123 ).…”
Section: Advanced Endoscopic Imaging Techniquesmentioning
confidence: 99%
“…Moreover, there exists a discrepancy among pathologists interpreting tissue samples. In a study from the Netherlands of patients diagnosed with LGD, 85% were downgraded to nondysplastic Barrett's esophagus (NDBE) after review by two expert GI pathologists [4]. Interestingly, in another international study, European pathologists had a higher concordance rate of interpretation than their US counterparts, which underlines the varied standards, experience, and clinical practice [5].…”
mentioning
confidence: 99%
“…This chapter aims to review some of these elements as well as the prognostic value of biomarkers for progression from BE to EAC. The importance of fulfilling the promise that these biomarkers hold is underscored by the notable increase in the risk of progression to cancer from 0.5% per year in non-dysplastic BE, to 13% in the setting of low-grade dysplasia, and to 40% in high-grade dysplasia (Curvers et al, 2010;Wani et al, 2009). …”
Section: Introductionmentioning
confidence: 99%